2013
DOI: 10.1016/j.crohns.2013.04.013
|View full text |Cite
|
Sign up to set email alerts
|

When do we dare to stop biological or immunomodulatory therapy for Crohn's disease? Results of a multidisciplinary European expert panel

Abstract: Background: Safety and economic issues have increasingly raised concerns about the long term use of immunomodulators or biologics as maintenance therapies for Crohn's disease (CD). Despite emerging evidence suggesting that stopping therapy might be an option for low risk patients, criteria identifying target groups for this strategy are missing, and there is a lack of recommendations regarding this question. Methods: Multidisciplinary European expert panel (EPACT-II Update) rated the appropriateness of stoppin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 36 publications
1
36
0
1
Order By: Relevance
“…Given the potential risks and burdens of long-term biological therapy, it has been asked how long it should be continued and when it can be safely stopped (10). However, the data on these issues are scarce and confl icting, and consequently generally accepted stopping rules have not yet been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Given the potential risks and burdens of long-term biological therapy, it has been asked how long it should be continued and when it can be safely stopped (10). However, the data on these issues are scarce and confl icting, and consequently generally accepted stopping rules have not yet been developed.…”
Section: Introductionmentioning
confidence: 99%
“…In order to be discontinued from IFX therapy, patients had to be in deep remission, defined as clinical and biochemical remission during an observation period of ≥2 years and endoscopic and histological remission before discontinuation of IFX [3]. Endoscopic and histological remission was defined as complete mucosal healing.…”
Section: Endpoints and Assessmentsmentioning
confidence: 99%
“…Existing guidelines have concluded that because of limited evidence, no recommendations can be made on when and in whom to discontinue TNFα-blocking therapy after having obtained clinical remission [1]. Currently, withdrawal of biological therapy is suggested in CD patients who have both complete mucosal healing and no biological evidence of inflammation [2,3]. However, several studies have shown that a substantial number of patients with IBD in stable remission relapsed within 2 years after stopping TNFα-blocking therapy.…”
mentioning
confidence: 99%
“…For de-escalation of any drug or cessation of corticosteroids or mesalamine, a confirmation of biological remission with biomarkers such as CRP or FC can be sufficient. However, if we are willing to stop immunosuppressants or anti-TNF drugs, a confirmation of mucosal healing by endoscopy seems desirable [44] .…”
Section: The Role Of Faecal Calprotectin In the Monitoring Of Ibdmentioning
confidence: 99%